The mediating role of work alienation on the relationship between leader-member exchange and job performance in the iraqi technical colleges and institutes - Muttar A.K.; Ahmad Z.A.; Siron R.B. (American Scientific Publishers, 2023)
The aim of this study is to empirically examine the mediating role of work alienation (WA) on the relationship between leader-member exchange (LMX) as independent variable and job performance (JP) as dependent variable among the academic staff in the Iraqi technical colleges and institutes. The topic has not gained significant attention in the educational management research arena. The study adopted a quantitative approach through survey instruments design and the population of the study was the academics in 18 technical colleges and institutes located in Baghdad and other governorates in Iraq. Structural equation modelling (SEM) was used to test the mediating effect of work alienation on the relationships between leader-member exchange and job performance. Based on a survey of 419 academics, the results revealed that work alienation mediates the relationship between leader-member exchange and job performance. 2015 American Scientific Publishers. All rights reserveds.